Ultrastructure of spores of Rhizopus nigricans after repeated freezing and thawing shocks - Necas, O; Gabriel, M (Folia microbiologica, 1980)
Disintegration of nuclear envelopes is the only ultrastructural change detectable by freeze-etching in dormant spores of the mould Rhizopus nigricans, both dry and swollen, subjected to repeated freezing and thawing. The increase of the number of freeze-inactivated spores corresponds well with the increase of the number of damaged nuclei. This fact led us to formulate a hypothesis that the structure of the nucleus is the primary target of the freezing or thawing damage. As other biomembranes are not damaged it may be assumed that the disintegration of the nuclear membrane is probably secondary. No changes in ultrastructure of metabolically activated spores could be detected, in spite of the fact that the spores lost their germinative ability. Thus, the mechanism of the freeze injury may be different in dormant and growing spores.
Keywords: endoplazmatické retikulum; jaderný obal; zmrazování; Spores, Fungal; Freeze Etching; Nuclear Envelope; mitochondrie; Endoplasmic Reticulum; leptání mrazem; Freezing; Mitochondria; spory hub; Rhizopus; cytoplazma; Cytoplasm